2018
DOI: 10.1002/pca.2795
|View full text |Cite
|
Sign up to set email alerts
|

Application of Box–Behnken design for ultrasound‐assisted extraction and recycling preparative HPLC for isolation of anthraquinones fromCassia singueana

Abstract: Introduction Cassia singueana Del. (Fabaceae) is a rare medicinal plant used in the traditional medicine preparations to treat various ailments. The root of C. singueana is a rich source of anthraquinones that possess anticancer, antibacterial and antifungal properties. Objective The objective of this study was to develop an ultrasound‐assisted extraction (UAE) method for achieving a high extraction yield of anthraquinones using the response surface methodology (RSM), Box–Behnken design (BBD), and a recycling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…5) implied that elevating both factors to their maximum values can favor better yields of the OPLE. This might be due to the use of a larger solventto-solid ratio that tends to promote a greater mass transfer of trapped plant solutes in cells into the surrounding medium, as previously described by similar studies [34,37]. This, in turn, led to an improved EY from the powdered OPL.…”
Section: The Mutual Interaction Of Process Variables Of Eymentioning
confidence: 63%
See 2 more Smart Citations
“…5) implied that elevating both factors to their maximum values can favor better yields of the OPLE. This might be due to the use of a larger solventto-solid ratio that tends to promote a greater mass transfer of trapped plant solutes in cells into the surrounding medium, as previously described by similar studies [34,37]. This, in turn, led to an improved EY from the powdered OPL.…”
Section: The Mutual Interaction Of Process Variables Of Eymentioning
confidence: 63%
“…Whilst, an extraction time of 30 min was seen as sufficient to enhance extraction of phenolic compounds from powdered OPL, a longer extraction time can allow a higher cavitation effect to physically disrupt plant cells [37] of OPL, thereby releasing higher contents of phenolic compounds into the extractive medium. The study found the value of TFC was the highest at 181.46 mg CAE/g.…”
Section: The Mutual Interaction Of Process Variables Of Tpcmentioning
confidence: 99%
See 1 more Smart Citation
“…Various analytical methods has been reported for the estimation of active phytoconstituents. It includes TLC , HPTLC , HPTLC/MS , HPLC , HPLC/MS/MS , LC/MS, GC/MS and GC/MS/MS.As per world health organisation recommendation High‐performance liquid chromatography coupled with UV detector is best suited for the pharmaceutical analysis. HPLC have been used widely in research and development and quality control sections in pharmaceutical industries .…”
Section: Introductionmentioning
confidence: 99%
“…Prep‐HPLC (preparative HPLC) can be used to isolate individual constituents from biological samples and natural products . This method has superior column efficiency, excellent separation reproducibility, efficient purification, and rapid online detection.…”
Section: Introductionmentioning
confidence: 99%